2016
DOI: 10.1097/md.0000000000002716
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Autologous Stem Cell Therapy for the Treatment of Lower Extremity Ulcers

Abstract: Primary studies in animal models and humans have suggested the therapeutic potential of autologous stem cell for treating chronic lower extremity ulcers. However, the results of pilot randomized controlled trials (RCTs) in humans have been inconsistent.A meta-analysis of RCTs was performed to evaluate the role of autologous stem cell-based therapy for lower extremity ulcers.Studies were identified during a systematic search of Medline, Embase, Cochrane's library, and references cited in related reviews and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…At present, no effective treatment for POF is currently available. Stem cells, as a multipotent cell type with the capacity of self-renewal and multilineage differentiation, have been proposed as a promising tool in tissue engineering for regenerative medicine ( 37 ). Their therapeutic potential has provided a novel strategy for preserving or recovering damaged ovarian function of women who receive chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, no effective treatment for POF is currently available. Stem cells, as a multipotent cell type with the capacity of self-renewal and multilineage differentiation, have been proposed as a promising tool in tissue engineering for regenerative medicine ( 37 ). Their therapeutic potential has provided a novel strategy for preserving or recovering damaged ovarian function of women who receive chemotherapy or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both studies had a mean age close to the age endpoint of 70 years, this may have interfered with the accuracy of the RCT study results. Jiang et al evaluated the effects of autologous stem cells on lower extremity ulcers and found autologous stem cell-based therapy was associated with better healing of lower extremity ulcers [ 33 ]; however, this study focused on patients with lower extremity ulcers that included diabetic patients and the non-diabetic population. Considering diabetes foot ulcers have specificity and distinctive risk factors, DFU patients should be seen as an independent observational target.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, BMSC and ADSC appear to have a positive effect on the healing of chronic wounds [ 38 ]. A systematic review and meta-analysis of BMSC in treatment of chronic leg ulcers [ 39 ] found that BMSC, like ADSC, are both safe and efficient. BMSC and ADSC seem to be alike in terms of differentiation capacities and immune-modulatory properties [ 40 ].…”
Section: Discussionmentioning
confidence: 99%